Formalism and parody in Bruno Schulz - Looby, Robert (Trinity College (Dublin, Ireland). Department of Russian & Slavonic Studies, 2002)
This thesis presents a systematic formal analysis of Bruno Schulz's prose fiction. It applies the methods of study developed by Formalists to aspects of the text ranging from minimal units such as choice of vocabulary to larger considerations such as the overall use and effect of metaphor. Its main finding is that Schulz's work may be read as a parody of Formalist thinking on the nature of literature. It also parodies Stanislaw Ignacy Witkiewicz's theory of Pure Form, which is similar to Formalism in several important respects. The parody is achieved by putting the opinions of Formalists into the mouth of a madman, and then presenting the reader with the results of putting Formalist precepts into action.
Keywords: Russian and Slavonic Studies, Ph.D.; Ph.D. Trinity College Dublin